Nonadaptive radiation: Pervasive diet specialization by drift in scale insects?. (1st October 2016) - Hardy, Nate B.; Peterson, Daniel A.; Normark, Benjamin B.
Abstract: At least half of metazoan species are herbivorous insects. Why are they so diverse? Most herbivorous insects feed on few plant species, and adaptive host specialization is often invoked to explain their diversification. Nevertheless, it is possible that the narrow host ranges of many herbivorous insects are nonadaptive. Here, we test predictions of this hypothesis with comparative phylogenetic analyses of scale insects, a group for which there appear to be few host‐use trade‐offs that would select against polyphagy, and for which passive wind‐dispersal should make host specificity costly. We infer a strong positive relationship between host range and diversification rate, and a marked asymmetry in cladogenetic changes in diet breadth. These results are consonant with a system of pervasive nonadaptive host specialization in which small, drift‐ and extinction‐prone populations are frequently isolated from persistent and polyphagous source populations. They also contrast with the negative relationship between diet breadth and taxonomic diversification that has been estimated in butterflies, a disparity that likely stems from differences in the average costs and benefits of host specificity and generalism in scale insects versus butterflies. Our results indicate the potential for nonadaptive processes to be important to diet‐breadth evolution and taxonomic diversification across herbivorous insects.